PRINCIPLES OF CALCULATION AND MONITORING OF STRESS-STRAIN STATE OF THE GRADE-SEPARATED TRAFFIC INTERCHANGES IN MINSK - Pastushkov, G. P.; Pastushkov, V. G. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The results of scientific accompaniment and monitoring of construction of the transport interchange at the intersection of Independence Avenue and Filimonova Street over tunnels and other structures of Minsk subway. In order to ensure (in three shifts) the construction and installation works at construction of transport interchange around a number of innovative technologies in both for designing and work performance has been used. Construction monitoring envisaged continuous control of deformations and stresses of constructions of underground tunnels in the online mode and data transmission to all interested organizations. The calculation model of the existing tunnels has been developed, which includes the design of the lining and the surrounding soil massif. A theory for calculating underground structures based on the deformation of materials of building structures and geomechanical models composing a soil massif has been proposed.
Keywords: transport structure; stress-strain state; traffic intersection; subway tunnel